The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1177/00220345890680020601
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride in Plaque Following Use of Dentifrices Containing Sodium Monofluorophosphate

Abstract: Previous work showed that plaque fluoride increased with increasing NaF content of mouthwashes following daily use. The main aim of this study was to test whether a similar relationship was detectable after regular use of dentifrices containing amounts of sodium monofluorophosphate equivalent to 1000, 1500, and 2500 micrograms F/g. Plaque was collected from three groups, each consisting of approximately 80 children, who had each used one of the dentrifrices for one year. Plaque fluoride increased significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 16 publications
4
25
0
Order By: Relevance
“…Bruun and Thylstrup [1984] observed an inverse relationship between mean salivary F concentration and mean caries prevalence in the permanent teeth of lifelong residents in high-(2.31 mg/l F) and low-(0.36 mg/l F) fluoridated water areas. Duckworth et al [1989] found a similar inverse relationship between mean plaque F content and mean 3-year caries increment for users of a series of TP that contained different amounts of sodium monofluorophosphate as the F source.…”
mentioning
confidence: 64%
“…Bruun and Thylstrup [1984] observed an inverse relationship between mean salivary F concentration and mean caries prevalence in the permanent teeth of lifelong residents in high-(2.31 mg/l F) and low-(0.36 mg/l F) fluoridated water areas. Duckworth et al [1989] found a similar inverse relationship between mean plaque F content and mean 3-year caries increment for users of a series of TP that contained different amounts of sodium monofluorophosphate as the F source.…”
mentioning
confidence: 64%
“…One clinical trial (Type 2) of dentifrices containing 1000, 1500 and 2500 ppm F reported that the fluoride concentration was more important than the amount of toothpaste applied. 28 Since very young children may swallow a large amount of toothpaste, 29,30 thereby increasing the risk of fluorosis, parents should supervise very young children and place only a small amount of toothpaste 31 (smear or pea size) on the brush. It is important to reinforce this advice since 31% of children aged 1.5 to 4.5 were reported to always brush their own teeth and 45% covered half the length of the brush or more.…”
Section: Amount Of Toothpastementioning
confidence: 99%
“…The concentration of fluoride in dental biofilm increases with the use of fluoride dentifrices, 10 fluoride mouthrinses, 11 and fluoridated drinking water.…”
mentioning
confidence: 99%